Adsorptive Removal of Methylene Blue onto ZnCl2 Activated Carbon from Wood Apple Outer Shell: Kinetics and Equilibrium Studies - N. Bhadusha; T. Ananthabaskaran (E-Journal of Chemistry)
Methylene blue dye removal from aqueous solution was investigated using ZnCl2 activated carbon prepared from wood apple outer shell (Limonia acidissima, biomass waste). Influence of agitation time, adsorbent dose, dye concentration, pH and temperature were explored. Two theoretical adsorption isotherms namely Langmuir and Freundlich were used to describe the experimental results. The Langmuir adsorption capacity (Qo) was found to be 35.1 mg/g and the equilibrium parameter (RL) values indicate favourable adsorption. The experimental data were well fitted with Langmuir isotherm model and pseudo second order kinetic model. Desorption studies showed that ion exchange mechanism might be involved in the adsorption process.